PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI DI PT YXZ - Nurandika, Salsabila; Romi, Mochamad Vrans (Politeknik Negeri Ambon, 2025)
Introduction: Occupational safety and health play a crucial role in supporting employee performance. One effective strategy to realize this is by implementing systematic safety and health protocols. In line with this, organizations are encouraged to ensure the availability of ongoing and routine health service facilities for all employees. This study seeks to examine the effect of occupational safety and health initiatives on the performance of production staff at PT YXZ.Methods: In this study, a quantitative method was applied, where data were obtained from 33 permanent employees working in the production unit. The data collection process involved structured interviews as well as the distribution of questionnaires. Afterward, the collected responses were analyzed using several techniques, including descriptive quantitative analysis, associative statistical methods, and multiple regression analysis.Results: The outcome of the analysis confirms that occupational safety and health factors collectively contribute positively and significantly to enhancing the performance of production employees at PT YXZ. Keywords: Occupational Safety, Occupational Health, Employee Performance.